GOOD GOVERNANCE: INITIATIVES AND CHALLENGES (International Journal of Food and Nutritional Sciences, 2022)
In contrast to good governance, governance is often used interchangeably with government or the act or process of ruling. International organisations and academics have embraced more inclusive definitions of the term. No one definition of "governance" exists to serve as a "convenient method for organising the literature," as Keefer (2009) points out. For example, Weiss (2000) includes seven definitions from seven organisations. The OECD (2009) also compiles seventeen more definitions as shown below.